Sustainable Value Co-Creation in Mobile Advertising in Cellular Telecommunication Industry: A Conceptual Framework - Joko Rurianto; Ujang Sumarwan; Budi Suharjo; Nur Hasanah (School of Business, IPB University (SB-IPB), 2021)
The growth of Mobile Internet services has changed the paradigm of telecommunication consumers from information- oriented toward social to communication- oriented. This change makes customers as part of the digital society, especially in Mobile Advertising services. Along with this change and the requirement for the company to win the competition, telecommunication providers must develop a business model of Mobile Advertising as a 'stage' that is easily accessible to all interested customers to this facility. In the concept of Service Dominant Logic, the company has no longer as a full control of value creation, but it must involve the customer in the process of value co-creation. The purpose of this research is to understandnding the landscape of Mobile Advertising services in telecommunication industry, understanding the existing model that can be build a model of Mobile Advertising services in the telecommunication industry, and understanding Mobile Advertising will influence on the value co-creation of the brand and corporate image. The research method using survey, exploratory, and systematic review. The research develops a model from the model of attributes and benefits of online community, model Consumer Engagement, model Attitude Toward Online Ads and model of Click Through Rate (CTR). Keywords: value co-creation, mobile advertising, consumer engagement, attitude toward online ads, click through rate (CTR)